FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA SKOR TOEFL MAHASISWA JURUSAN TEKNIK SIPIL FT- UNP TAHUN MASUK 2016 - Annisa Najmi; Drs. Juniman Silalahi, M.Pd (CIVED, 2019)
Abstract—This research aims to find out the factors that influence the low TOEFL score of the students of the Civil Engineering Department of FT-UNP in the year 2016. This type of research is descriptive. This research was conducted in the Civil Engineering Department of the FT-UNP. Respondents in this study were students of the 2016 Civil Engineering Department of the FT-UNP who had taken the TOEFL test with a score of <400. Data collection techniques in this study used questionnaires. While the sampling technique used is total random sampling. In this study the number of respondents was 56 students. The results of this study indicate that the factors that influence the low TOEFL score of the Civil Engineering Department FT-UNP students in 2016 as a whole are in the moderate category and the most dominant factor affecting the low TOEFL score of students is a technical factor.Keywords: TOEFL Score, Students, Civil Engineering